2004
DOI: 10.1128/jcm.42.1.458-460.2004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Environmental Distributions of Legionella Strains in France Are Different

Abstract: In France, the clinical distribution of Legionella species and serogroups does not correspond to their environmental distribution. Legionella pneumophila serogroup 1 is more prevalent among clinical isolates (95.4%) than in the environment (28.2%), whereas L. anisa is more frequent in the environment (13.8%) than in the clinical setting (0.8%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
117
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(130 citation statements)
references
References 14 publications
9
117
1
3
Order By: Relevance
“…The phylogenetic inference of mip gene sequences showed three different serogroup clusters related to L. pneumophila isolates from man-made systems, suggesting that these isolates are well adapted to environmental survival. These data are in accordance with previous reports in others regions around the world, where limited genetic variability of environmental isolates of L. pneumophila in the water systems and the prevalence of one genotype of this bacterium in a large proportion of man-made aquatic environments were reported (7,11,12,24,34,47). Although Legionella species other than L. pneumophila may occur in man-made systems, one explanation for the apparent spread of L. pneumophila observed in this The species L. gormanii (ATCC 33297) was used as outgroup.…”
Section: Discussionsupporting
confidence: 83%
“…The phylogenetic inference of mip gene sequences showed three different serogroup clusters related to L. pneumophila isolates from man-made systems, suggesting that these isolates are well adapted to environmental survival. These data are in accordance with previous reports in others regions around the world, where limited genetic variability of environmental isolates of L. pneumophila in the water systems and the prevalence of one genotype of this bacterium in a large proportion of man-made aquatic environments were reported (7,11,12,24,34,47). Although Legionella species other than L. pneumophila may occur in man-made systems, one explanation for the apparent spread of L. pneumophila observed in this The species L. gormanii (ATCC 33297) was used as outgroup.…”
Section: Discussionsupporting
confidence: 83%
“…Little is known about the distribution of Legionella species and serogroups in the environment. A recent study investigating 259 clinical and 3128 environmental strains isolated in France from 2001 to 2002 showed that L. pneumophila Sg1 accounts for 28.2% of environmental Legionella in contrast to 95.4% among clinical isolates (Doleans et al 2004). Thus, the distribution of environmental L. pneumophila Sg1 differs significantly from the distribution of clinical L. pneumophila Sg1 strains.…”
mentioning
confidence: 83%
“…Thus, the distribution of environmental L. pneumophila Sg1 differs significantly from the distribution of clinical L. pneumophila Sg1 strains. Furthermore, species like Legionella anisa, Legionella dumofii, or Legionella feeleii relatively frequently colonize water distribution systems but are rarely implicated in human disease (Muder and Yu 2002;Yu et al 2002;Doleans et al 2004). From these reports one can hypothesize that the high percentage of L. pneumophila Sg1 strains in human disease is not due to predominance in the environment, but rather connected with higher virulence of these strains for humans.…”
mentioning
confidence: 92%
“…Up to now, only 20 species have been associated with human disease, and Legionella pneumophila appears responsible for more than 90 % of reported cases of Legionnaires' disease [9][10][11].…”
Section: Introductionmentioning
confidence: 99%